The Stress led to Depression: The Nearest Danger in the Present Society - Punyakitphokin, Wananya (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The stress and the depression can be found in all ages, genres, races and religions. This condition happens when the individual encounters with lots of problems in life. This causes the disappointment, the sadness, and the expectation which was not responded; or it comes from the sickness of some diseases, the loss of beloved persons and so on. These situations affect the persons to feel bored, mad, dishearten, depressed, disappointed and worthless. If these problems were more collected with being solved, it could lead the personal depression. Yet, if those persons can keep tracking on the problems and the negative feeling happening to them in the early stage, they can urgently search for the relieving method and protect the problems before they become the serious mental problem. This article presented the dimensions of the depression of persons which were caused by various stress in daily life. The author showed the content about the stress relating to the which was the beginning of collecting stress and led to the mental illness, on the observation and protect themselves and people around them who might be in risk of the depression so that the society realized the importance on protecting and taking care for themselves in the early stage before the problems in terms of emotions occupied their mind until they were in the depressed condition at the end.